Morphological and molecular characterization of actinic lentigos reveals alterations of the dermal extracellular matrix. (1st December 2017) - Warrick, E.; Duval, C.; Nouveau, S.; Bastien, P.; Piffaut, V.; Chalmond, B.; Ortonne, J‐P.; de Lacharrière, O.; Bernerd, F.
Summary: Background Actinic lentigos (AL) are benign hyperpigmented skin lesions associated with photoageing. Despite their high prevalence, biological mechanisms driving their formation remain unclear. Objectives To provide new insights about the physiopathology of AL through a comprehensive description of their histological and molecular features. Methods Quantitative analysis of dermoscopic images was used to select AL containing elongated patterns, predicted to display a highly deformed dermal–epidermal junction (DEJ), on the back of the hands of 15 Caucasian women. Biopsies from lesional and adjacent nonlesional (NL) areas were processed for histological analysis or gene expression profiling. Results Histological staining confirmed a drastic deformation of the DEJ in AL, with deep epidermal invaginations into the dermis. Although the melanin content was significantly higher in AL compared with NL epidermis, the distribution of melanocytes along the DEJ was unchanged. Transcriptomic analysis revealed a signature of 529 genes differently expressed in AL vs. NL skin. Alteration of epidermal homeostasis was confirmed by the dysregulation of keratinocyte proliferation and differentiation markers. Surprisingly, canonical genes involved in melanogenesis were not significantly modulated in AL. A striking finding was the overexpression of a large group of genes involved in dermal extracellular matrix organization and remodelling. Dermal alterations were confirmed by immunolabellings on AL and NL sections. Conclusions Drastic disorganization of the cutaneous structure in AL is accompanied by a specific molecular signature revealing alterations in both epidermal and dermal compartments. In particular, our results suggest that local modifications of the dermal extracellular matrix might contribute to hyperpigmentation in AL.